Role of PBAF and Mediator kinase module in the RELA-dependent activation of CXCL1–3 inflammation genes of the NF-kB pathway - Feoktistov, Alexey V.; Grigel, Anton A.; Zolin, Ivan A.; Yurkina, Darya M.; Tvorogova, Anna V.; Azieva, Asya M.; Georgieva, Sofia G.; Soshnikova, Nataliya V. (Frontiers in Immunology, 2026)
IntroductionThe transcription of inflammatory genes is rapidly induced by extracellular stimuli through coordinated actions of transcription factors and large coactivator complexes. However, the mechanistic interplay between specific chromatin remodelers and kinase modules in driving the transcriptional burst of early inflammatory genes remains poorly understood. This study investigates the roles of the PBAF chromatin remodeling complex and the Mediator kinase module (MKM) in activating NF-κB-dependent CXCL1, CXCL2, and CXCL3 chemokine genes.MethodsWe employed a combination of molecular and genomic techniques. Protein-protein interactions were analyzed via co-immunoprecipitation (co-IP). Transcriptional outputs of CXCL1-3 genes were measured by quantitative mRNA analysis. Chromatin immunoprecipitation (ChIP) was used to assess the occupancy of RNA polymerase II (Pol II), its elongating form (Pol II-S2P), the MKM subunit CDK8, and the PBAF complex (via its BAF200 subunit) at target gene promoters. Functional contributions of the complexes were dissected using siRNA-mediated knockdown of BAF200 (PBAF) and small-molecule inhibition of the MKM.ResultsPBAF and MKM physically interact with each other and with the NF-κB subunit RELA, and both complexes additively contribute to the transcriptional activation of CXCL1-3 genes. Knockdown of the PBAF-specific subunit BAF200 resulted in the loss of the entire PBAF complex from chromatin, a reduction in total Pol II and CDK8 promoter occupancy, and consequently, impaired gene induction. In contrast, MKM inhibition did not affect PBAF recruitment but specifically reduced the level of elongating Pol II-S2P and transcriptional activation. These data indicate non-redundant, stage-specific functions.DiscussionOur results demonstrate that the PBAF complex and the Mediator kinase module regulate distinct, sequential steps in the transcription cycle of CXCL1-3 genes. PBAF is critical for the initial promoter recruitment or stabilization of the transcription machinery, while MKM primarily facilitates the transition into productive elongation. Their additive positive effect and physical interaction suggest a coordinated mechanism where PBAF establishes a permissive chromatin context, enabling subsequent MKM-dependent phosphorylation events that drive the transcriptional burst of key inflammatory chemokines.